2022
DOI: 10.1186/s13148-022-01275-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting male fertility from the sperm methylome: application to 120 bulls with hundreds of artificial insemination records

Abstract: Background Conflicting results regarding alterations to sperm DNA methylation in cases of spermatogenesis defects, male infertility and poor developmental outcomes have been reported in humans. Bulls used for artificial insemination represent a relevant model in this field, as the broad dissemination of bull semen considerably alleviates confounding factors and enables the precise assessment of male fertility. This study was therefore designed to assess the potential for sperm DNA methylation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 125 publications
3
22
0
Order By: Relevance
“…These findings are in alignment with similar studies in humans and domesticated animals (Costes et al, 2022;Rotondo et al, 2021;Štiavnická et al, 2022;Sujit et al, 2020;Takeda et al, 2021), which have all highlighted the critical role of DNA methylation in the proper development and functioning of sperm cells. Candidate genes that we identified from gene networks built from DMclusters in sperm are well-studied and known to be involved in the regulation of developmental onset via epigenetic transcriptional repression in humans and mice, specifically in the multi-protein complexes formed by JARID2 and EZH2 in PRC2 (Fischer et al, 2022;Margueron & Reinberg, 2011;Pasini et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in alignment with similar studies in humans and domesticated animals (Costes et al, 2022;Rotondo et al, 2021;Štiavnická et al, 2022;Sujit et al, 2020;Takeda et al, 2021), which have all highlighted the critical role of DNA methylation in the proper development and functioning of sperm cells. Candidate genes that we identified from gene networks built from DMclusters in sperm are well-studied and known to be involved in the regulation of developmental onset via epigenetic transcriptional repression in humans and mice, specifically in the multi-protein complexes formed by JARID2 and EZH2 in PRC2 (Fischer et al, 2022;Margueron & Reinberg, 2011;Pasini et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…DNA methylation has been linked as both a cause and consequence to variation in gene regulation (Pacis et al., 2019), has been studied prolifically as a key biomarker for aging and disease for several decades (Mattei et al., 2022; Prado et al., 2021), and is associated with variation in reproductive metrics in humans, model laboratory organisms, and commercially relevant species (Rotondo et al., 2021; Sujit et al., 2020). Recent studies have identified an increasingly important role for DNA methylation variation in sperm to fertility metrics in the ex situ breeding of domesticated animals (Costes et al., 2022; Štiavnická et al., 2022; Takeda et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine sperm-related traits such as semen quality, fertility, etc., that are critical for bovine reproduction can be influenced by environmental, regulatory, and epigenetic factors [ 60 ]. Recent studies focus on bull fertility traits such as sire conception rate (SCR), but semen quality was rarely studied as a result of the direct discard of unqualified semen before AI [ 61 , 62 ].…”
Section: The Impacts Of Sperm Epigenome On Complex Traits In Cattlementioning
confidence: 99%
“…Costes et al [ 61 ] used the methylome variations to establish the predictive model using a Random Forest approach and demonstrated that the fertility status of approximately 75% of the bulls could be predicted consistently by the facultative sperm DNA methylation signature of 107 fertility-related differentially methylated cytosines (DMCs). They suggested that the less biased selected DMCs should be utilized to build the predictive model for better performance because the fertility-related DMC patterns are not conserved in all samples [ 61 ]. Based on the aforementioned methylation arrays, the new genetic merit estimations for sperm quality could be obtained by considering SNPs and DMCs simultaneously in the refined genomic selection equations (Fig.…”
Section: Application Of Sperm Epigenetic Modification In Cattle Breedingmentioning
confidence: 99%
“…They compared fertile with subfertile bulls and found 490 fertility-related differentially methylated regions, most of which were hypomethylated in subfertile bulls. Based on these sperm DNA methylation patterns, they developed a bull fertility prediction model which presented 72% accuracy rates (Costes et al, 2022). 2018) also compared offspring from young (120 days old) and aged male mice (>630 days old).…”
Section: Sperm Dna Methylation In Agingmentioning
confidence: 99%